2020
DOI: 10.1016/j.ebiom.2020.102676
|View full text |Cite
|
Sign up to set email alerts
|

ZHX2 restricts hepatocellular carcinoma by suppressing stem cell-like traits through KDM2A-mediated H3K36 demethylation

Abstract: Background: Liver cancer stem cells (CSCs) are critical determinants of HCC relapse and therapeutic resistance, but the mechanisms underlying the maintenance of CSCs are poorly understood. We aimed to explore the role of tumor repressor Zinc-fingers and homeoboxes 2 (ZHX2) in liver CSCs. Methods: CD133 + or EPCAM + stem-like liver cancer cells were sorted from tumor tissues of HCC patients and HCC cell lines by flow cytometry. In addition, sorafenib-resistant cells, tumor-sphere forming cells and side populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…For instance, increased KDM3A expression was associated with tumour recurrence after resection, 119 while the upregulation of LSD1/KDM1, KDM5B, KDM6B, KDM4B and KDM2A has been related to tumour aggressiveness and poor prognosis. [120] , [121] , [122] , [123] , [124] The transcriptional programmes influenced by the overexpression of KDMs are complex to elucidate. The activity of these enzymes may have differential effects on gene expression depending on the specific histone residue on which they act.…”
Section: Epigenetic Alterations In Hepatocarcinogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, increased KDM3A expression was associated with tumour recurrence after resection, 119 while the upregulation of LSD1/KDM1, KDM5B, KDM6B, KDM4B and KDM2A has been related to tumour aggressiveness and poor prognosis. [120] , [121] , [122] , [123] , [124] The transcriptional programmes influenced by the overexpression of KDMs are complex to elucidate. The activity of these enzymes may have differential effects on gene expression depending on the specific histone residue on which they act.…”
Section: Epigenetic Alterations In Hepatocarcinogenesismentioning
confidence: 99%
“…For example, LSD1/KDM1 and KDM4B, both upregulated in HCC, can remove repressive H3K9 methyl marks, while concomitantly, LSD1/KDM1 and KDM4B can eliminate H3K4 and H3K36 active methyl marks, respectively. 59 Nevertheless, several pro-tumorigenic mechanisms triggered by KDMs in HCC have been elucidated, including the promotion of stem cell-like traits by KDM6B and KDM2A, 122 , 124 and the maintenance of glycolytic metabolism, stemness and drug resistance by LSD1/KDM1. 125 , 126 …”
Section: Epigenetic Alterations In Hepatocarcinogenesismentioning
confidence: 99%
“…Studies have shown that KDM2A as a lysine demethylase was highly overexpressed in many cancers, such as breast cancer (8,29), gastric cancer (9), lung cancer (30) and hepatoma (31). In addition, it can be downregulated by tumor microenviroment (28).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that ZHX2 might have other downstream targets than miR‐24‐3p. In fact, ZHX2 inhibits the development of HCC through many reported routes, such as inhibiting cell proliferation, the cell cycle, and cell migration [21,43]. Further efforts are needed to explore alternative mechanistic routes for ZHX2 inhibiting the development of HCC.…”
Section: Discussionmentioning
confidence: 99%